The University of the West Indies and Caribbean tertiary level institutions : increasing access, maintaining quality - Whiteley, Peter (2000)
Examines the need for greater articulation between UWI and regional TLIs, with particular reference to increasing access to students from the non-campus countries. Outlines the various forms of articulation that UWI supports and discusses the uses of Associate Degrees. Outlines slao, the methodology used by UWI to establish an articulation agreement with another TLI. Highlights the need to maintain the quality of regional tertiary-level education programmes and considers the efforts being made to create a regional accreditation mechanism. Makes suggestions for possible further developments in the regional tertiary education system.